Intimate Style Used by The Characters In The Incredibles Movie - I Gusti Ayu Komang Lia Pratiwi; Ni Wayan Suastini (Wanastra: Jurnal Bahasa dan Sastra, 2023)
The aim of this research is analysed intimate style that used by the characters in The Incredibles movie and the social factors that influencing the characters to use intimate style would be analysis also. The researcher did this research use descriptive qualitative method and also using observation method to collect the data. The researcher used theory from Martin Joos and Holmes. The result of this research presented descriptively. This research found 15 intimate language style in the movie those are addressee with 3 data, extraction with 4  data, jargon with 2 data, close friend relationship with 2 data, and family relationship with 5 data and also found the social factors that influencing the characters to use intimate style such as participant, topic, setting and function.  The participants of this movie have very close relationship such as family relationship because the topic of the movie is about family superheroes. The conversation in the movie also mostly occurs in informal situation. The utterances that produce by the characters have various function. But mostly, the characters produce the utterances to show their intimacy and closeness each other.